Magnetic Resonance Imaging–Guided Focused Ultrasound Positioning System for Preclinical Studies in Small Animals - Drakos, Theoharis; Giannakou, Marinos; Menikou, Georgios; Damianou, Christakis A. (My University, 2021)
Objectives: A positioning device compatible with magnetic resonance imaging (MRI) used for preclinical studies in small animals was developed that fits in MRI scanners up to 7 T. The positioning device was designed with two computer-controlled linear stages. Methods: The positioning device was evaluated in an agar-based phantom, which mimics soft tissues, and in a rabbit. Experiments with this positioning device were performed in an MRI system using the agar-based phantom. The transducer used had a diameter of 50 mm, operated at 0.5 MHz, and focused energy at 60 mm. Results: Magnetic resonance thermometry was used to assess the functionality of the device, which showed adequate deposition of thermal energy and sufficient positional accuracy in all axes. Conclusions: The proposed system fits in MRI scanners up to 7 T. Because of the size of the positioning device, at the moment, it can be used to perform preclinical studies on small animals such as mice, rats, and rabbits.
Keywords: Magnetic resonance imaging; Mouse; Positioning; Ultrasound